2015
DOI: 10.1080/13688804.2015.1015512
|View full text |Cite
|
Sign up to set email alerts
|

Television—the Housewife's Choice? The 1949 Mass Observation Television Directive, Reluctance and Revision

Abstract: This article considers the responses of women, many of whom describe themselves as housewives, in the 1949 Mass Observation Television Directive, in order to interrogate some of the broader assumptions around television's relationship with 'the housewife' as key to its success. Against the backcloth of social histories revising ideas about gender, modernity and suburbia in the post-war period, this article considers some of the ways in which initial reluctance towards television was recorded and negotiated. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the magazines that Spigel studied, she charts how the tone and address to this "ideal housewife" also had to take into account the fears around television's potential to disrupt domestic harmony and even to generate youth delinquency, as well as the ways in which the housewife's work in the home needed to be accommodated by the new medium. Whilst ideas of the "ideal home" suggest a mythical figure of the ideal (and seduced) housewife, historical work demonstrates that television adoption, especially in the earliest phases, needed to be brokered in order to take into account the competing demands of women's roles in the production of family life and the home (Helen Wood 2015).…”
Section: The Ideal Female Consumer and The Productive Role Of The Housewifementioning
confidence: 99%
See 1 more Smart Citation
“…In the magazines that Spigel studied, she charts how the tone and address to this "ideal housewife" also had to take into account the fears around television's potential to disrupt domestic harmony and even to generate youth delinquency, as well as the ways in which the housewife's work in the home needed to be accommodated by the new medium. Whilst ideas of the "ideal home" suggest a mythical figure of the ideal (and seduced) housewife, historical work demonstrates that television adoption, especially in the earliest phases, needed to be brokered in order to take into account the competing demands of women's roles in the production of family life and the home (Helen Wood 2015).…”
Section: The Ideal Female Consumer and The Productive Role Of The Housewifementioning
confidence: 99%
“…While the above studies are so valuable to tracing television's gendered relationship to material culture and the ways that women have been explicitly and especially addressed by television, it still leaves some questions as to how might we access women audiences of the time? This article builds on research previously conducted by Helen Wood (2015) which used the 1949 Mass Observation Directive to explore women's feelings about the arrival of television (which, at this earlier time, was non-commercial). It found that, contrary to dominant assumptions about women's enthusiastic embrace of the medium, there was actually considerable reluctance from women.…”
Section: Finding Audiences In the Mass Observations Archivementioning
confidence: 99%
“…A broadcast by Kate Aitken on the last day of 1948 that listed notable women of the year set the pattern for a consumerist address, which linked the unnamed woman-at-home with public sphere, primarily through consumption practices but also in a surreal political configuration of the nation-state and world politics. Sponsored by Ogilvie Flour Mills, Aitken's talks simultaneously combined radically different, and at times conflicting, scales-domestic, local, regional, national, and international-by situating the listener as being connected to a mediated world of celebrities and commodities in ways that both drew on existing frameworks from print media (Clampin 2017) and anticipated television's uptake in the home during the 1940s and 1950s (Wood 2015).…”
Section: They Tell Me: Claire Wallacementioning
confidence: 99%
“…1 Concerns were raised around how portrayals of violence influenced young and malleable minds, stoking fears about its links with delinquency as well as its destabilizing effects on the rhythms of family life and gender relations. In Britain, it was frequently criticized as an agent of American cultural imperialism and consumerism (Wood 2015;Moran 2014;Thomson 2013: chapter 4;Oswell 2002;Thumim 2002;Corner 1991). Less work has been devoted to the television set as an object and the activity of watching it (Black 2005: 548).…”
mentioning
confidence: 99%